Hubungan Rasio Neutrofil Limfosit (RNL) Dengan Skor Gleason Pasien Kanker Prostat - andriyani, fatimah; Sari, Puspita; Wahyuni, Rossa Dwi; Fitriana, Yuli; Tutu, Arlin Rinni; Aristo, . (E-Jurnal Medika Udayana, 2024)
One of the diseases of the prostate gland is prostate cancer. This cancer causes abnormal growth of prostate cells. Trigger factors for the emergence of this cancer are age, genetics, obesity, a diet high in fat and animal fiber. The neutrophil lymphocyte ratio (RNL) is recommended as a biomarker for inflammatory diseases and also in a number of cancers, one of which is prostate cancer. The higher of the RNL value indicates that the cancer prognosis is getting worse. This study aims to determine the relationship between RNL and Gleason score in prostate cancer patients at Undata Hospital, Palu 2019-2022, In this study, the researcher used an analytic observational research design with a cross-sectional design. Samples were taken using total sampling with a total of 33 samples from 2019 to 2022. Samples were taken using total sampling with a total of 33 samples from 2019 to 2022. Based on the Spearman correlation test, the total significance was obtained between RNL and gleason score (r=;-0.105 P=0.562. ). There is no significant relationship between RNL and gleason score in prostate cancer patients Keywords : Neutrofil to lymphocyte ratio, prostate cancer, Gleason score.